'Re betha trupa': the construction and negotiation of identity amongst the bakgatlha ba mosetlha with an emphasis on diturupa cultural commemoration - Motlhamme, Mojuta Steven (My University, 2021)
Diturupa is a cultural commemoration that happens annually on the 26th of December in Makapanstad. It is primarily based on military drilling and parades done by soldiers. It incorporates Setswana traditional elements from the locality of Makapanstad amongst the Bakgatlha Ba Mosetlha community. This study is a critical analysis of how Diturupa shapes the identity and ethnicity of Bakgatlha ba Mosetlha community in Makapanstad. Diturupa has been sustainable for the past hundred years as a community based initiative rooted in custom and rituals linked to a diverse identity. Diturupa is linked to the SS Mendi tragedy where black South African soldiers lost their lives. It is also a commemoration of those who fought in World War I and World War II. Diturupa represents an inclusive commemoration rooted in a spirit of diversity, creativity, and togetherness. It is rooted in respect for chieftaincy and bringing the community together in the festive season. Diturupa has a rich material culture starting with the kilt (Scotch), kettle drums, Tempedi and soldier uniforms that are worn on the 26th of December. This material culture is rooted in Setswana culture but incorporates western elements to create a diverse identity. Performance is at the heart of Diturupa and brings together various elements to recreate and remember those who perished and sacrificed their lives on the many battlefields of the world wars. The legacy of Diturupa is an ongoing project that continues to be written and re written. It is safe to say that Diturupa will be with us for generations and represents a truly unique cultural heritage identity in the trans provincial geopolitical region of Moretele.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021